METODE SOSIODRAMA UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK CERITA ANAK PADASISWA KELAS V SDNEGERI96 PEKANBARU - Afrida, Afrida (Jurnal Pendidikan Guru, 2017)
This research is based on the low level of students ability in listening to childrens story. The purpose of this study is to improve the ability to listen to childrens stories that include using the method of Sociodrama (Role Playing) students of class V SDN 96 Pekanbaru. This research was conducted in class V SDN 96 Pekanbaru with 33 students, 13 men and 20 women. This study uses classroom action research methods conducted in 2 (two) cycles with 4 (four) stages: planning, action, observation and reflection as a basis for re-planning in the next cycle. The ability to listen to childrens stories obtained from preliminary data is with a percentage of 51.51% who complete a score above 65 according to KKM standards. After applying the first role cycle method I with the percentage 63,63%, second meeting of cycle I with the percentage 75,75%, second meeting of cycle II with the percentage 84,84%. Based on the results of research can be concluded that the application of methods of sociodrama (role playing) in learning Indonesian language can improve the ability to listen to childrens stories on students V SD Negeri 96 Pekanbaru can be accepted